The Effectiveness of Multimedia Assisted Project-Based Learning and Self-Regulation on Learning Outcomes of Light Vehicle Engineering Skills - Probowati, RR. Rina; Samsudi, Samsudi; Ahmadi, Farid (Innovative Journal of Curriculum and Educational Technology, 2021)
Project-based learning is used as a reference for developing the ability to create and update because it is seen as having characteristics that effectively direct students to investigate essential ideas and questions, framed through the discovery process, able to accommodate the different needs and interests of students, directing freedom in making products or services and presentations that exceed what the teacher hopes, requires the ability to think creatively, critical thinking, the ability of information to find and write conclusions and present material, and relate to real and authentic problems and the latest issues. Multimedia is a medium for delivering information that contains complete material because it presents the material in writing and is equipped with videos and evaluation tools. The next difference is self-regulation as the variable studied in addition to learning outcomes. The results showed that project-based learning improved student learning outcomes, as evidenced by the Wilcoxon test results with a significance value = < 0.05. Learning outcomes shown from knowledge tests and performance tests are influenced not only by the students' ability to practice based on the theory being learned but also by their ability to self-regulate (self-regulation). The correlation between self-regulation and knowledge learning outcomes is 0.465, and the correlation between self-regulation and practical learning outcomes is 0.890, with the significance of each test of 0.000 < 0.05. It shows that the learning outcomes of cooling system knowledge and practices are influenced by self-regulation. Project-based learning tools assisted with multimedia are effective as a learning model for class XI students of light vehicle engineering at Public Vocational High Schools in Semarang City are classified as valid. Multimedia-assisted project-based learning is effective as a learning model for class XI students of light vehicle engineering at Public Vocational High Schools in Semarang City. This multimedia-assisted project-based learning can improve learning outcomes, achieve completeness and be better than project-based learning. Self-regulation affects class XI students' learning outcomes of light vehicle engineering at Public Vocational High Schools in Semarang City.